A família na educação de jovens e adultos - SOUSA, Lucidalva dos Santos (2020)
The work was developed in a school in the city of Belémin the group of the first stage of the Education of Young and Adults (EJA), using disciplinary activity, with the theme "The family", putting in question how families were in the past and how it is today, starting the conversation with two questions, which is family to them, and the other if they have family support. The present theme sought to provide the student of the EJA a reflection on their family structure and the other families, relating their family context and in this way seek knowledge about the subject so that there is awareness of respect among the different families, realizing that the Family configuration has undergone transformations over the years, reflecting on what is Family; The differences and similarities of a family and the real importance of this family to the human being, contributing to the students doing the activities proposals using reading and writing and their mathematical knowledge in the activity. Students participating in the activity were six, with ages ranging from 20 to 50 years, night shift.